2004
DOI: 10.1007/s00467-003-1328-5
|View full text |Cite
|
Sign up to set email alerts
|

Citrate anticoagulation in pediatric continuous venovenous hemofiltration

Abstract: Regional citrate anticoagulation has become a common alternative to systemic heparinization in adult continuous venovenous hemofiltration (CVVH) practice. We report our experience with the technique in critically ill children. We carried out a retrospective chart review of a 22-bed pediatric intensive care unit. CVVH with pre-filter citrate and systemic calcium replacement infusions was performed according to a strict protocol in nine consecutive critically ill children. All charts were reviewed for patient ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…No randomized controlled trials and very few observational studies have been carried out in pediatric patients on CRRT treated with citrate [3, 4]. Only 6 randomized controlled trials comparing citrate and heparin anticoagulation have been published in adult patients [712].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No randomized controlled trials and very few observational studies have been carried out in pediatric patients on CRRT treated with citrate [3, 4]. Only 6 randomized controlled trials comparing citrate and heparin anticoagulation have been published in adult patients [712].…”
Section: Discussionmentioning
confidence: 99%
“…However, few observational studies have been published about citrate anticoagulation in pediatric patients [3, 4] and no one has compared the efficacy of heparin and citrate for anticoagulation in critically ill children on CRRT. This is the objective of our study.…”
Section: Introductionmentioning
confidence: 99%
“…Bunchman et al reported filter lifetimes of approximately 72 h on average, in a series of 14 patients on continuous venovenous hemofiltration with dialysis [ 89 ] and in another series of 9 patients on continuous venovenous hemofiltration [ 90 ], without hemorrhagic complications. In a study of 9 patients, Elhanan et al reported filter survival of up to 5 days [ 91 ].…”
Section: Area 2: Technical Aspectsmentioning
confidence: 99%
“…Citrate is thought to have the benefits of decreasing inflammation as well as the need for blood products and allows longer circuit survival [ 9 14 ]. Most of the citrate is cleared by the CRRT circuit; however, about 1 mmol/kg spills over into the patient’s circulation [ 15 , 16 ]. In the setting of liver failure, metabolism of citrate is impaired and accumulation can lead to a citrate toxicity-often known as “citrate lock” -where there is continued chelation of serum ionized calcium [ 17 ].…”
Section: Introductionmentioning
confidence: 99%